The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1990
DOI: 10.1177/0265407590072002
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Sexual Communication in Marriage: Links to Sexual Satisfaction and Dyadic Adjustment

Abstract: This study explored the relationships among sexual communication satisfaction, sexual satisfaction and dyadic adjustment in marital relationships. A total of 402 married individuals responded to a mail survey. Results indicated that satisfaction with sexual communication was significantly and positively associated with sexual satisfaction, dyadic adjustment, dyadic satisfaction, dyadic cohesion, affectional expression and dyadic consensus. Based upon an examination of partial correlations it is proposed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
5

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 10 publications
10
86
1
5
Order By: Relevance
“…Other studies30, [32][33][34][35] have demonstrated that open and honest communication is essential to a satisfying sexual relationship. In close relationships, both partners have the responsibility to communicate their views as honestly and accurately as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies30, [32][33][34][35] have demonstrated that open and honest communication is essential to a satisfying sexual relationship. In close relationships, both partners have the responsibility to communicate their views as honestly and accurately as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The extent and quality of (sexual) communication within a relationship are often considered as important determinants of the overall relationship satisfaction and the level of intimacy between partners (Greeff & Malherbe, 2001). In addition, research has shown that intimate communication is associated with the quality of the sexual relationship between partners (e.g., Cupach & Comstock, 1990;Montesi et al, 2013). Thus, when discussing the association between adverse relationship experiences and victims' current sexual well-being it is also highly interesting to have a clearer view on the interactional processes between partners such as sexual communication.…”
Section: Sexual Communication Sexual Communication Refers To the Intmentioning
confidence: 99%
“…Research has discovered that reciprocal sexual self-disclosure contributes to greater relational and sexual satisfaction (Byers & Demmons, 1999;Cupach & Comstock, 1990;Lawrance & Byers, 1995;MacNeil & Byers, 2005;Meeks, Hendrick, & Hendrick, 1998;Sprecher & Cate, 2004) perhaps by way of better understanding a partners' past sexual experiences, sexual health, and sexual likes/dislikes (Baumeister, Stillwell, & Wotman, 1990;Cupach & Metts, 1991;MacNeil & Byers, 2009). …”
Section: Potential Benefits Associated With Disclosure About Past Sexmentioning
confidence: 99%